Detection of central circuits implicated in the formation of novel pain memories - Birklein, Frank; Upadhyay, Jaymin; Granitzka, Julia; Bauermann, Thomas; Baumgärtner, Ulf; Breimhorst, Markus; Treede, Rolf-Detlef (Journal of pain research, 2016)
Being able to remember physically and emotionally painful events in one's own past may shape behavior, and can create an aversion to a variety of situations. Pain imagination is a related process that may include recall of past experiences, in addition to production of sensory and emotional percepts without external stimuli. This study aimed to understand 1) the central nervous system processes that underlie pain imagination, 2) the retrieval of pain memories, and 3) to compare the latter with visual object memory. These goals were achieved by longitudinally investigating brain function with functional magnetic resonance imaging in a unique group of healthy volunteers who had never experienced tooth pain. In these subjects, we compared brain responses elicited during three experimental conditions in the following order: imagination of tooth pain (pain imagination), remembering one's own house (object memory), and remembrance of tooth pain following an episode of induced acute tooth pain (pain memory). Key observations stemming from group-level conjunction analyses revealed common activation in the posterior parietal cortex for both pain imagination and pain memory, while object and pain memory each had strong activation predominantly within the middle frontal gyrus. When contrasting pain imagination and memory, significant activation differences were observed in subcortical structures (ie, parahippocampus - pain imagination > pain memory; midbrain - pain memory > pain imagination). Importantly, these findings were observed in the presence of consistent and reproducible psychophysical and behavioral measures that informed on the subjects' ability to imagine novel and familiar thoughts, as well as the subjects' pain perception.